Outlaw tales of the Old West : fifty true stories of desperados, crooks, criminals, and bandits - Turner, Erin H., 1973- (TwoDot, 2016)
Outlaws Tales of the Old West features fifty stories of rustlers and robbers, crimes of passion, and some of the wannabe outlaws who couldn't quite pull it off, some of the most fascinating--and least known--badmen to roam the lawless West. Massacres, mayhem, and mischief fill the pages of Outlaw Tales of the Old West, with compelling legends of some of the most despicable desperadoes in history. Ride with horse thieves and cattle rustlers, duck the bullets of murderers, plot strategies with con artists, and hiss at lawmen turned outlaws.